PENGARUH LAYANAN POS GIRO MOBILE TERHADAP KEPUASAN PELANGGAN PT. POS INDONESIA (PERSERO) KABUPATEN PAMEKASAN - Rachman Hakim; Kiptiyah Kiptiyah (Fakultas Ekonomi Universitas Yos Soedarso, 2021)
This study aims to determine the effect of the mobile giro post service on customer satisfaction at PT. Pos Indonesia (Persero) Pamekasan. The research sample used 83 respondents. The method used in this research is quantitative method. The results showed that the variables efficiency, reliability, fulfillment and privacy together had an effect on customer satisfaction at PT. Pos Indonesia (Persero) Pamekasan. As for the results of the t test calculation, the efficiency, reliability and fulfillment variables have no effect on the customer satisfaction variable. Meanwhile, the privacy variable has a positive and significant effect on customer satisfaction.Keywords : Efficiency; Reability; Fulfillment; Privacy; Customer Satisfaction.